Interleukin-6 Trajectory and Secondary Infections in Mechanically Ventilated Patients With Coronavirus Disease 2019 Acute Respiratory Distress Syndrome Treated With Interleukin-6 Receptor Blocker. (3rd February 2021) - Vazquez Guillamet, M. Cristina; Kulkarni, Hrishikesh S.; Montes, Kevin; Samant, Maanasi; Shaikh, Preet A.; Betthauser, Kevin; Mudd, Philip A.; Reynolds, Daniel; O'Halloran, Jane; Lyons, Patrick; McEvoy, Colleen; Vazquez Guillamet, Rodrigo
Abstract : Objectives: To describe the infectious complications and interleukin-6 trajectories in mechanically ventilated patients with coronavirus disease 2019. Design: Retrospective cohort study. Setting: ICUs at Washington University-Barnes Jewish Hospital in St. Louis, MO. Participants: All consecutive patients admitted to the medical ICU and requiring mechanical ventilation from March 12, 2020, to April 21, 2020, were included. Interventions: Tocilizumab, an interleukin-6 receptor blocker, was prescribed at the discretion of the treating physicians to patients with a clinical picture compatible with cytokine release syndrome. Measurements: All the patients were followed to death or hospital discharge. Demographic and laboratory data were collected retrospectively from the electronic medical record. Interleukin-6 levels were measured at days 0, 3, 7, 14, and 21. Infections were divided into culture positive and culture negative (clinically suspected and treated). The main outcomes were infectious complications and interleukin-6 levels at different points in time. Results: Forty-three patients with respiratory failure secondary to coronavirus disease 2019 were on mechanical ventilation during the study period. Twenty-seven (68%) were male, and 31 (72.1%) were African-American. Median Charlson score was 2 (interquartile range, 0–4). Median Pao2/Fio2 was 171.5 (122–221) on the day of mechanical ventilation initiation, and 13 patients (30.2%) required vasopressors. C-reactive protein was 142.7 (97.7–213.7), d-dimer 1, 621 (559–13, 434), and Acute Physiology and Chronic Health Evaluation-II 11 (9–15). Interleukin-6 levels at admission were 61 pg/mL (interquartile range, 28.6–439 pg/mL). Patients treated with tocilizumab had higher levels of interleukin-6 at each measurement (days 0, 3, 7, 14, and 21) compared with patients receiving standard of care. Both groups reached peak interleukin-6 levels at day 7. Administration of tocilizumab was associated with a trend toward increased risk of infection. Conclusions: Interleukin-6 levels peak at day 7 in patients with severe coronavirus disease 2019 pneumonia requiring mechanical ventilation and follows a similar trajectory in patients with coronavirus disease 2019 pneumonia requiring mechanical ventilation irrespective of treatment with interleukin-6R blockers. Interleukin-6 levels continued to rise in nonsurvivors, in comparison with survivors, where the rise in interleukin-6 levels was followed by a decline.